Expression of Legumain Correlates with Prognosis and Metastasis in Gastric Carcinoma - Guo, Pengtao (Public Library of Science, 2013)
OBJECTIVE: Legumain, a novel asparaginyl endopeptidase, has been observed to be highly expressed in several types of tumors, which may play a vital role in carcinogenesis. However, there is no study investigating the relationship among Legumain expression, clinicopathologic, biological variables and patient prognosis in gastric carcinoma. METHODS: In this study, a tissue microarray (TMA) containing 282 samples of primary gastric cancer was assessed for Legumain expression by immunohistochemistry. The TMA included 98 lymph node metastasis samples. The protein expression levels of Legumain were evaluated by Western blot analysis. RESULTS: Cytoplasmic immunoreactivity of Legumain was over-expressed in gastric cancer compared with paired normal gastric mucosa. Increased Legumain levels were significantly correlated with clinical stage, presence of distant metastasis. Legumain was significantly over-expressed in primary gastric cancer with metastasis than without metastasis. Patients with Legumain-positive localized tumors had lower 5-year overall survival (OS) than those with Legumain-negative tumors. Multivariate survival analysis showed that Legumain was an independent prognostic marker for OS (HR 1.459, 95% CI 1.251–1.703, P = 0.007). CONCLUSIONS: Legumain expression could serve as a prognostic biomarker in patients at risk of developing metastasis or recurrence with gastric carcinoma.